Universal Religious Learning Model (Studi Pengamalan Al Qur’an Surat An-Nahl Ayat 125): Studi pengamalan Alquran surat An-Nahl Ayat 125 - Almas, Afiq Fikri (TAWAZUN: Jurnal Pendidikan Islam, 2024)
Humans cling to the Quran as a source of education, teaching a way of life, and offering many insights into the existence of life that brings life. Many aspects of religious education are also contained in the Qur'an, one of which is the management of the learning process by implementing a universal model for all human groups. The subject matter in this paper is (1) The essence of a universal religious learning model is contained in Q.S. An-Nahl verse 125, (2) The implementation of a religious learning model using the Bil Hikmah model, the Al Mau'idzhah Hasanah model and the Mujaadalah Billatii Hiya Ahsan model is very relevant for junior and senior high school levels. This research uses descriptive qualitative method and tahliliy or tajzi'iy interpretation approach, as well as book survey or literature study used to collect the opinions of mufasirin and equipped with data sources from relevant books. The results of this study found several novelty, namely: (1) Based on the practice of the Qur'an letter An-Nahl verse 125 in the study of education there are three universal religious learning models which include educational models through bil-hikmah, educational models through Al Mau'idzah Al Hasanah, and educational models through Mujaadalah Billatii Hiya Ahsan. (2) The Universal Religious Learning Model (URLM) can be applied in Islamic religious studies in particular and can also be applied in learning religions other than Islam through material content according to their respective beliefs and religions in junior high school or high school. Abstrak Manusia berpegang teguh pada Alquran sebagai sumber pendidikan, mengajarkan cara hidup, dan menawarkan banyak wawasan tentang keberadaan hidup yang menghidupkan. Aspek pendidikan agama juga banyak terkandung di dalam Alquran yang salah satunya adalah pengelolaan proses pembelajaran dengan mengimplementasikan model universal untuk semua kelompok manusia. Pokok bahasan dalam tulisan ini yaitu (1) Esensi model pembelajaran agama yang universal terkandung dalam Q.S. An-Nahl ayat 125, (2) Implementasi model pembelajaran agama dengan menggunakan model Bil Hikmah, model Al Mau’idzhah Hasanah dan model Mujaadalah Billatii Hiya Ahsan sangat relevan untuk tingkat SMP dan SMA sederajat. Penelitian ini menggunakan metode deskriptif kualitatif dan pendekatan tafsir tahliliy atau tajzi'iy, serta book survey atau studi literatur digunakan untuk mengumpulkan pendapat para mufasirin dan dilengkapi dengan sumber data dari kitab yang relevan. Hasil penelitian ini menemukan beberapa novelty yaitu: (1) Berdasarkan pengamalan dari Alquran surat An-Nahl ayat 125 dalam kajian pendidikan terdapat tiga model pembelajaran agama yang universal yang meliputi model pendidikan dengan melalui bil-hikmah, model pendidikan dengan melalui Al Mau'idzah Al Hasanah, dan model pendidikan dengan melalui Mujaadalah Billatii Hiya Ahsan. (2) Universal Religious Learning Model (URLM) dapat diterapkan dalam pembelajaran-pembelajaran agama Islam khususnya dan juga dapat diterapkan dalam pembelajaran agama selain agama Islam melalui konten materi sesuai keyakinan dan agamanya masing-masing di SMP ataupun SMA.